2014
DOI: 10.3390/ijerph110606052
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Natural Recovery: Youth Experience of Social Inclusion through Green Care

Abstract: The aim of this study has been to investigate the effects of Green Care services for youth in vulnerable situations risking social exclusion. Green Care enterprises represent alternative arenas in which people can work with animals, agriculture and other tasks related to nature. We interviewed nine persons, aged 17–27, working in three different places, two or more times over a two-year period. We looked at essential beneficial factors in order to better understand how the “green” element could add to more tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
3
33
0
1
Order By: Relevance
“…Nearly all participants reported that they were pleased or very pleased with the nature-based services. These results are in accordance with previous studies using qualitative approaches on similar target groups in Norway (Ellingsen-Dalskau et al, 2016b;Granerud & Eriksson, 2014;Kogstad et al, 2014;Pedersen et al, 2012a). An interesting proposal for further research would be to compare the satisfaction rates among this group with similar groups participating in other types of services.…”
Section: Expectations and Satisfactionsupporting
confidence: 93%
“…Nearly all participants reported that they were pleased or very pleased with the nature-based services. These results are in accordance with previous studies using qualitative approaches on similar target groups in Norway (Ellingsen-Dalskau et al, 2016b;Granerud & Eriksson, 2014;Kogstad et al, 2014;Pedersen et al, 2012a). An interesting proposal for further research would be to compare the satisfaction rates among this group with similar groups participating in other types of services.…”
Section: Expectations and Satisfactionsupporting
confidence: 93%
“…Following our sample, 10 categories of users have been identified, and two of these categories stand out ( Figure 4 ): people suffering from psychological health illnesses such as depression, burnout and/or stress (e.g., [ 35 , 42 ]; in 30% of the studies), and people suffering from mental health illnesses, such as cases of dementia, schizophrenia, personality and behavioral disorders and other mental health problems (e.g., [ 43 , 44 ]; in 21% of the studies). Other publications focused on children and young people at risk of exclusion (e.g., those with behavioral problems or with dysfunctional family backgrounds; such as [ 11 ]; in 8% of the studies), on people with learning disabilities (e.g., [ 45 ]; in 7% of the studies), on elderly populations (e.g., [ 22 ]; in 7% of the studies), and on people suffering from physical disabilities or physical health illnesses (e.g., people with chronic muscle pain, coronary and pulmonary diseases or cancer; [ 46 ]; in 6% of the studies). Finally, a more limited number of studies focused on people suffering from addictions (4%), offenders (e.g., [ 47 ]; in 3% of the studies), people experiencing long-term unemployment (e.g., [ 48 ]; in 1% of the studies), and refugees and displaced people (e.g., [ 49 ]; in 1% of the studies).…”
Section: Resultsmentioning
confidence: 99%
“…This concept has been formalized in the academic world through the study of social-ecological systems [ 9 ]. Following the biophilia theory [ 10 ], this connection should be more important and integrated into our lives, but the ability to connect with and understand nature often depends on our experiences as children, and such experiences should be reinforced in our society [ 11 ]. In addition to the biophilia theory, Kaplan’s attention restoration theory [ 12 ] and Ulrich’s psycho-evolutionary theory [ 13 ] should be highlighted, as these theories defend and explain why and how our surrounding natural environment influences our lives and is important for us.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on participants with clinically diagnosed mental illnesses have demonstrated improvements in mental health scores after spending time on a care farm (Sempik et al 2014). Farms provide a platform where people can find meaning to their lives as well as relationships that grow and become an important part of their social wellbeing (Hassink et al 2010;Iancu et al 2014;Kogstad et al 2014;Leck et al 2015).…”
Section: Introductionmentioning
confidence: 99%